Characterization of the dizocilpine binding site on the nicotinic acetylcholine receptor - Arias, Hugo Rubén (2001)
Although the dissociative anesthetic dizocilpine [(+)-MK-801] inhibits nicotinic acetylcholine receptor (AChR) function in a noncompetitive manner, the location of the dizocilpine binding site(s) has yet to be clearly established. Thus, to characterize the binding site for dizocilpine on the AChR we examined 1) the dissociation constant (Kd) and stoichiometry of [3H]dizocilpine binding; 2) the displacement of dizocilpine radioligand binding by noncompetitive inhibitors (NCIs) and conversely dizocilpine displacement of fluorescent and radiolabeled NCIs from their respective high-affinity binding sites on the AChR; and 3) photoaffinity labeling of the AChR using 125I-dizocilpine. The results establish that one high-affinity (Kd = 4.8 μM) and several (3-6) low-affinity (Kd = ∼ 140 μM) binding sites exist for dizocilpine on the desensitized and resting AChR, respectively. The binding of the fluorescent NCIs ethidium, quinacrine, and crystal violet as well as [3H]thienylcyclohexylpiperidine was inhibited by dizocilpine on desensitized AChRs. However, Schild-type analyses indicate that only the inhibition of quinacrine in the desensitized state seems to be mediated by a mutually exclusive action. Photoaffinity labeling of the AChR by 125I-dizocilpine was primarily restricted to the α1 subunit and subsequent mapping revealed that the principal sites of labeling are localized to the M4 (∼70%) and M1 (30%) transmembrane domains. Collectively, the data indicate that the high-affinity dizocilpine binding site is not located in the lumen of the ion channel but probably near the quinacrine binding locus at a nonluminal domain in the AChR desensitized state.